The Role of Proteases in Determining Stomatal Development and Tuning Pore Aperture: A Review - Fanourakis, Dimitrios; Nikoloudakis, Nikolaos; Pappi, Polyxeni; Markakis, Emmanouil; Doupis, Georgios; Charova, Spyridoula N; Delis, Costas; Tsaniklidis, Georgios (My University, 2020)
Plant proteases, the proteolytic enzymes that catalyze protein breakdown and recycling, play an essential role in a variety of biological processes including stomatal development and distribution, as well as, systemic stress responses. In this review, we summarize what is known about the participation of proteases in both stomatal organogenesis and on the stomatal pore aperture tuning, with particular emphasis on their involvement in numerous signaling pathways triggered by abiotic and biotic stressors. There is a compelling body of evidence demonstrating that several proteases are directly or indirectly implicated in the process of stomatal development, affecting stomatal index, density, spacing, as well as, size. In addition, proteases are reported to be involved in a transient adjustment of stomatal aperture, thus orchestrating gas exchange. Consequently, the proteases-mediated regulation of stomatal movements considerably affects plants' ability to cope not only with abiotic stressors, but also to perceive and respond to biotic stimuli. Even though the determining role of proteases on stomatal development and functioning is just beginning to unfold, our understanding of the underlying processes and cellular mechanisms still remains far from being completed.
Keywords: Pore aperture; Stomata; Stomatal density; Stomatal length; Stomatal spacing; Transpiration; Water loss